Implementation of Character Education through the Teaching Campus Program as an Effort to Strengthen Students’ Character Values - Irwan Irwan; Muslimah Muslimah; Abdul Azis; Masdani Masdani (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
Character education is a fundamental aspect in the formation of students' personalities, especially in the midst of the challenges of globalization and technological developments that have the potential to affect the moral values of the young generation. This research seeks to explain how character education is implemented through the Teaching Campus Program as an effort to reinforce students’ character values at SDN 16 Dasan Agung Baru Mataram. It also aims to identify the specific values being cultivated and to examine both the supporting and inhibiting factors in the process. Employing a qualitative approach with a case study design, the participants were selected purposively, consisting of the school principal, Islamic Religious Education teachers, Teaching Campus participants, and fourth-grade students. Data were gathered through participant observation, in-depth interviews, and documentation, with data validity ensured by triangulating sources and techniques. The findings reveal that character education at SDN 16 Dasan Agung Baru Mataram is integrated into learning activities, routine practices, and religious programs such as congregational prayers, morning literacy sessions, flag ceremonies, imtaq activities, and the enforcement of school discipline. Teachers serve as key role models (uswah hasanah) in instilling values among students. The values emphasized include religiosity, discipline, responsibility, honesty, cooperation, tolerance, and environmental awareness. Factors that support the implementation of character education involve the commitment of principals, teachers, and parents, the presence of a positive school culture, and consistent habituation programs. Meanwhile, the inhibiting factors include the influence of the environment outside school and social media, limited time for carrying out activities, and the lack of awareness of some students in applying character values. This study concludes that the Teaching Campus Program contributes positively to strengthening the implementation of character education in elementary schools.